CULTURAL INFLUENCES ON PREGNANCY PRACTICES IN THE SULAWESI REGION: A LITERATURE REVIEW - Andi Suriyani; Dewi Hestiani K (JOURNAL OF HUMANITIES AND SOCIAL STUDIES, 2024)
Pregnancy is a complex biological process, involving significant physiological and psychological changes in a woman's body. In addition to biological aspects, pregnancy is also influenced by socio-cultural factors that shape the experiences of pregnant women. In South Sulawesi, traditional cultural beliefs and practices are still very much present, including rituals, dietary restrictions, and the use of traditional birth attendants. This literature review examines how cultural practices in Sulawesi influence pregnancy care. The research used the PRISMA method to identify relevant literature from various academic databases. Results show that certain dietary restrictions and rituals can have both good and bad effects on maternal and foetal health. Cultural beliefs, such as the use of mantras and the important role of traditional birth attendants, provide spiritual and psychological support, but can also hinder adequate nutrition. These findings emphasise the need for integration between modern health practices and traditional beliefs to improve maternal health. This study will help health providers design more effective and culturally sensitive programmes to improve maternal and infant health in Sulawesi.